Pengaruh Model Pembelajaran Project Based Learning Terhadap Konsentrasi Belajar Siswa Mata Pelajaran Pendidikan Pancasila Kelas V SD Islam Plus YLPI - Nurul Cahya Utami; Zaka Hadikusuma Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by factors that interfere with students' ability to concentrate during class, namely, lack of interest in the material and boredom with the lesson. In addition, teachers who do not use enough learning models can hinder the teaching and learning process. Project Based Learning (PjBL) is one of the innovative teaching models that motivates students to learn in a context and facilitates collaboration through complex activities that encourage students to be more active and motivated. The purpose of this study was to describe the effect of the project based learning model on students' concentration in learning Pancasila Education subjects. This type of research uses a Quantitative Pre-Experimental One Group Pretest-Posttest Design approach. The results of this study by collecting pretest and posttest questionnaire data on learning concentration with a total of 21 students. The results of the Hypothesis Test using the normality test the Shapiro Wilk formula, the Pretest value is 0.362> 0.05 and the Posttest value is 0.180> 0.05, so the data is normally distributed. Meanwhile, the hypothesis test with the t-test sig value (2-tailed) 0.000 < 0.05, and the simple linear regression test value 0.000 < 0.05, then the X variable has an influence on the Y variable, then H0 can be decided to be rejected and Ha can be accepted. Thus, the project based learning model has an influence on the concentration of students' learning of the Pancasila education subject in class V of SD Islam Plus YLPI